ORÇAMENTO PARTICIPATIVO: O Processo de Implementação em São Luís - Cruz Neto, Nilo (2009)
This work has as study object the process of implementation of the Participatory Budgeting (PB) in the city of São Luís, experience initiated in the year of 1997. The work presents the main characteristics of the PB, as for the format, to the coordination and the dynamics of the participatives instances, and tries to understand the determinative factors of its success/failure, being based on variable gifts in literature. The study sample that, not obstante the Participatory Budgeting in some cities has favored the participation of the citizens in the questions that involve its material conditions of life, in São Luís it did not arrive if to configure as a real instrument of deliberative democracy and cooperation between the municipal public power and the population. Diverse limitations, indicated throughout the text, had been determinative and made it difficult the process since its implementation, having disabled a transformation of the employee's stock sharing plan in action accomplish. For the accomplishment of the work bibliographical research and in documentary sources had been carried through, beyond accomplishment of interviews with participants of the process of implementation of the PB in São Luís.